Surgery Versus Interferon Alpha-2b Treatment Strategies for Ocular Surface Squamous Neoplasia: A Literature-Based Decision Analysis. Issue 5 (May 2016) - Siedlecki, Andrew N.; Tapp, Stephanie; Tosteson, Anna N. A.; Larson, Robin J.; Karp, Carol L.; Lietman, Thomas; Zegans, Michael E.
Abstract : Purpose: To compare treatment strategies for ocular surface squamous neoplasia (OSSN), ranging from surgical excision to empiric topical interferon alpha-2b (IFN-α2b). Methods: A decision model was constructed to determine which of 4 treatment strategies minimized expected persistence/recurrence of disease in patients with OSSN: excision followed by repeat excision for positive surgical margins, excision followed by IFN-α2b for positive margins, incisional biopsy followed by IFN-α2b for positive biopsies, and empiric treatment with IFN-α2b. Probabilities were estimated from literature published between 1983 and 2015. Expected values for the probability of recurrence could range from 0 (no persistence/recurrence) to 1 (persistence/recurrence). Sensitivity analyses were performed for each variable. Results: Excision followed by IFN-α2b for positive margins was estimated to minimize persistence/recurrence of OSSN (expected value 0.13 versus 0.17 for empiric IFN-α2b, 0.22 for excision-only, and 0.30 for incisional biopsy-directed IFN-α2b). The optimal strategy was sensitive to 3 variables: efficacy of IFN-α2b, recurrence after negative surgical margins, and accuracy of excisional biopsy. Conclusions: In our decision analysis using studies published between 1983 and 2015, surgical excision followed by IFN-α2b for positive margins is the favored strategy for minimizing persistence/recurrence of OSSN. Future prospective studies would add to the certainty of these conclusions.